Cemento-ossifying fibroma in an 8-year-old patient: a case report - Morales Martínez, Karen Lilian (2025)
Cemento-ossifying fibroma is a true neoplasm that belongs to the group of benign fibro-osseous lesions. It is characterized by the replacement of bone tissue with fibrous connective tissue that undergoes mineralization, and its diagnosis can be challenging due to its similarity to other lesions. Its origin has been theorized to be odontogenic or from the periodontal ligament, as it can produce cementum-like material within the bone trabeculae. We present the case of an 8-year-old female patient diagnosed with a cemento-ossifying fibroma in the mandible, measuring 50 × 32 mm, who underwent lesion excision along with the dental organs, without recurrence during follow-up. This neoplasm is relatively rare in patients in the third and fourth decades of life and even less common in pediatric patients; therefore, its diagnosis must be carried out comprehensively.